Combined effect of toe out gait and high tibial osteotomy on knee adduction moment in patients with varus knee deformity. (March 2017) - Whelton, C; Thomas, A; Elson, DW; Metcalfe, A; Forrest, S; Wilson, C; Holt, C; Whatling, G
Abstract: Background: Gait adaptations, including toe out gait, have been proposed as treatments for knee osteoarthritis. The clinical application of toe out gait, however, is unclear. This study aims to identify the changes in Knee adduction moment in varus knee deformity assessing toe out gait as an alternative to high tibial osteotomy, and if any change in dynamic loading persists post operatively, when anatomical alignment is restored. Methods: Three-dimensional motion analysis was performed on 17 patients with medial compartment knee osteoarthritis and varus deformity prior to undergoing high tibial osteotomy, 13 patients were assessed post-operatively, and results compared to 13 healthy controls. Findings: Pre-operatively, there was no significant difference between natural and toe out gait for measures of knee adduction moment. Post high tibial osteotomy, first (2.70 to 1.51% BW·h) and second peak (2.28 to 1.21% BW·h) knee adduction moment were significantly reduced, as was knee adduction angular impulse (1.00 to 0.52% BW·h·s), to a healthy level. Adopting toe out gait post-operatively reduced the second peak further to a level below that of healthy controls. Interpretation: Increasing the foot progression angle from 20° (natural) to 30° in isolation did not significantly alter the knee adduction moment or angular impulse. This suggests that adopting a toe out gait, in isolation, in an already high natural foot progression angle, is not of benefit. Adopting toe out gait post-operatively, however, resulted in a further reduction in the second peak to below that of the healthy control cohort, however, this may increase lateral compartment load. Highlights: Toe out gait suggested method of reducing the knee adduction moment. First to study toe out gait and high tibial osteotomy. No significant reduction in first or second peak knee adduction moment or adduction angular impulse with toe out gait. High tibial osteotomy significantly reduced both knee adduction moment peaks to within healthy limits. Toe out gait post high tibial osteotomy lowered knee adduction moment to below healthy controls.